Bone Marrow and Kidney Findings at Odds: A Case Report and Review of Literature of Divergent Pathology in Chronic Myeloid Leukemia - Ranga, Shivani; Chennamaneni, Rachana; Konatam, Meher Lakshmi; Prakasham, Thejeswar N.; Sivakumar, Swetha; Uppin, Megha S.; Gundeti, Sadashivudu (Indian Journal of Medical and Paediatric Oncology, 2025)
Chronic myeloid leukemia (CML) is a hematologic malignancy driven by the BCR-ABL1 fusion gene, which results in the abnormal proliferation of myeloid cells. The disease typically has two phases: chronic (CP) and blast crisis (BC). Extramedullary blast crisis (EBC) in CML refers to the presence of blast cells in extramedullary sites, irrespective of the blast proliferation occurring in the bone marrow. Renal infiltration of blasts as the initial presentation of CML is exceedingly rare. We present a case of a 51-year-old man with renal failure. Renal biopsy showed myeloperoxidase staining blasts, with bone marrow in CP. Based on the presence of EBC, the patient was diagnosed with CML in BC, despite the CP in the bone marrow, a rare occurrence that challenges conventional diagnostic pathways.
Keywords: acute kidney injury; blast phase; chronic myeloid leukemia; chronic phase; extramedullary blast crisis; tyrosine kinase inhibitors